A CRITIC TO THE OBJECTIVES OF THE GLOBAL PUBLIC PROCUREMENT INITIATIVES IN THE CONTEXT OF THEWTO - Laguado Giraldo, Roberto; Universidad Warwick (Editorial Pontificia Universidad Javeriana y Facultad de Ciencias Jurídicas, 2005)
This comment focuses in the previous works and tendencies of the WTO and the Agreement on Government Procurement. Its basic concern is how developing countries are neglecting accession to the treaty arguing lack of real access to the international procurement markets and loss opportunities for implementing developing policies.The paper places vis-à-vis two leading aims pursued by public procurement trade agreements —national welfare and market access—, in the context of the WTO and overviews whether the transparency approach will lead to globalize the Public Procurement market. It describes the status of WTO Public Procurement negotiations and how likely will the Agreement on Government Procurement prove towards a multilateral trade system. Public procurement regulation as a tool for development and its relation with market access trade policies will also be addressed as well as to what extent works on transparency in public procurement are entirely vital and useful for the global trade initiatives.